Options trading in agricultural futures markets: A reasonable instrument of risk hedging, or a driver of agricultural price volatility? - Thomas Glauben; Sören Prehn; Tebbe Dannemann; Bernhard Brümmer; Jens-Peter Loy (Leibniz Institute of Agricultural Development in Transition Economies (IAMO), 2014)
Options trading is increasingly important in more volatile agricultural markets. Options allow for unilateral hedging of price risks, e. g. against falling prices only, and are an indispensable risk management instrument for farmers and grain dealers. Concerns that soaring options trading could spark incremental volatility of international agricultural commodity prices have not been empirically verified to date. Econometric assessments for the MATIF grain maize market suggest that option trading does not have a volatility increasing effect. – – Auf volatileren Agrarmärkten gewinnt der Handel mit Optionen zunehmend an Bedeutung. Optionen gestatten die einseitige Absicherung von Preisrisiken, z. B. nur gegen fallende Preise, und stellen ein zunehmend bedeutenderes Instrument für das Risikomanagement von Landwirten und Landhändlern dar. Befürchtungen, dass der zunehmende Handel mit Optionen zu einer erhöhten Volatilität internationaler Agrarrohstoffpreise führen könnte, sind bisher empirisch nicht nachzuweisen. Ökonometrische Schätzungen für den MATIF-Körnermaismarkt weisen darauf hin, dass kein volatilitätserhöhender Effekt durch den Optionshandel festzustellen ist.
urn:nbn:de:gbv:3:2-54888
Keywords: 330